2018
DOI: 10.1039/c8cy00742j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic properties of pristine and defect-engineered Zr-MOF-808 metal organic frameworks

Abstract: Defect-engineered Zr-MOF-808 are superior catalysts for Meerwein–Ponndorf–Verley reduction of (bulky) carbonyls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 36 publications
7
88
0
1
Order By: Relevance
“…This fact evidences the presence of two different Brönsted acid sites, associated with µ 3 -OH group of metal cluster. 63,58 We also observe a band at 2138 cm -1 related to physisorbed CO. 61,62 Moreover, when these samples were pre-treated at 250 °C under high-vacuum ( Figure 8. c and d) for release of formate linkers 54 and/or dehydroxylation of the cluster, 56 two bands are identified at 2155 cm -1 , corresponding to the interaction of CO with Brönsted acid sites, and at 2177 cm -1 , being assigned to Lewis acid centres. This means that one of the types of Brönsted acid sites was lost with the dehydroxylation, generating Lewis acid sites.…”
Section: Role Of Acid Sites In Mofs Catalytic Performancementioning
confidence: 68%
See 2 more Smart Citations
“…This fact evidences the presence of two different Brönsted acid sites, associated with µ 3 -OH group of metal cluster. 63,58 We also observe a band at 2138 cm -1 related to physisorbed CO. 61,62 Moreover, when these samples were pre-treated at 250 °C under high-vacuum ( Figure 8. c and d) for release of formate linkers 54 and/or dehydroxylation of the cluster, 56 two bands are identified at 2155 cm -1 , corresponding to the interaction of CO with Brönsted acid sites, and at 2177 cm -1 , being assigned to Lewis acid centres. This means that one of the types of Brönsted acid sites was lost with the dehydroxylation, generating Lewis acid sites.…”
Section: Role Of Acid Sites In Mofs Catalytic Performancementioning
confidence: 68%
“…Thermodynamically, in some case, the number of defects in the material structure is related to its stability [56, 57] . In MOFs, which are crystalline solids in all their infinite network, these defects could be introduced spontaneously or in a controlled manner, modulating their final properties [58, 52] . Active sites are coordinatively unsaturated metal centers (CUS) present in the MOF intrinsically by design and additionally as a consequence of defects derived from uncoordinated ligands to the metal center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is possible that MOF-808 could also have missing linker defects, which would impact the reactivity of this material. 42 We have shown that a low barrier pathway for DMMP hydrolysis exists when there are two-adjacent missing linkers in UiO-67. It is not known experimentally whether these specific defect types exist, but theoretical work indicating that multiple missing linkers in a unit cell are energetically favored when they are localized (in the same tetrahedral cage) rather than being distributed.…”
Section: Resultsmentioning
confidence: 86%
“…MOF‐based materials, including pristine MOFs, MOF composites (e.g., C 3 N 4 /MOF composite, metal nanoparticles@MOF, and TiO 2 /MOF composite), and MOF‐derived materials are well studied for the catalysis purposes. For most MOFs are insulator, design MOF‐based materials as efficient catalysts for CO 2 reduction, their charge mobility, and electronic conductivity should be carefully considered.…”
Section: Synthetic Approaches For Mofsmentioning
confidence: 99%